The Influence of the Use of Instagram Social Media, Lifestyle, Financial Attitude, and Ease of Digital Payment Facilities in Mobile Banking on Consumptive Behavior in Students During the Covid-19 Pandemic Through the Role of Financial Literacy as a Modera: Pengaruh Penggunaan Media Sosial Instagram, Gaya Hidup, Sikap Keuangan, dan Kemudahan Fasilitas Digital Payment pada Mobile Banking terhadap Perilaku Konsumtif Mahasiswa di Masa Pandemi Covid-19 Melalui Peran Literasi Keuangan sebagai Variabel - Trisuci, Choirunnisa Mutiara; Abidin, Fityan Izza Noor (Indonesian Journal of Law and Economics Review, 2022)
This study discusses the Influence of Instagram, Lifestyle, Financial Attitude, and Ease of Mobile Banking on Consumptive Behavior Through the Role of Financial Literacy as a Moderating Variable. The existence of consumptive behavior experienced by students causes them to have a bad financial attitude in their consumption behavior and will affect their financial condition in the future if they do not improve their financial literacy. The purpose of this study is to determine whether financial literacy can influence students to reduce consumptive behavior. This type of research is descriptive with a quantitative approach. The data analysis technique is SEM-PLS 3.0. The sampling technique used purposive sampling with a sample of 63 respondents. The results showed that Instagram had an effect on Consumptive Behavior, Lifestyle had an effect on consumptive behavior, Financial Attitude had an effect on consumptive behavior, Ease of mobile banking had no effect on Consumptive Behavior, Financial Literacy did not moderate Instagram on Consumptive Behavior, Financial Literacy moderated Lifestyle on Consumptive Behavior, Financial Literacy does not moderate Financial Attitude towards Consumptive Behavior, Financial Literacy does not moderate Ease of mobile banking on Consumptive Behavior.